Characteristics and Teaching Styles of an Effective English Teacher: A Case Study at SMPN 1 Pangkajene - Riska Arnas; Muhammad Azwar Assiddiq (CV. Eureka Murakabi Abadi, 2021)
The objectives of the research are to find out the characteristics of the effective English teacher and the types of teaching style at junior high school 1 Pangkajene. This research employed qualitative research design applying case study. The participant of this research was an English teacher of Junior High School 1 Pangkajene. The data of this research were collected by employing classroom observation and field notes. Classroom observation was used to get data deeply about the characteristics and teaching styles of an effective English teacher. Field notes used as supporting data for observation. The result of this research showed that (1) there were nine characters of the effective English teacher namely; Great loyalty and commitment, high responsive, to the students utilities, the capabilities in teaching which is compatible to the disposed, originative and entertaining, good at encouragement and stimulating, and self-reflection (2) Type of teachers teaching styles used by the effective English teacher in classroom were facilitator style, personal model style, delegator style, impressive style and self-check style. The researcher concluded that there were nine sub-categories the effective English teacher and there were five types of teachers teaching style used by the effective English teacher at Junior high school 1 Pangkajene.